GPs’ perspective on End-of-Life Care – an evaluation based on the German version of the General Practice End of Life Care Index - van Baal, Katharina (Ger Med Sci, 2020)
Objective: General practitioners (GPs) play a key role in the provision of general outpatient palliative care (AAPV) for the majority of patients at the end of life. The aim of this study was to evaluate the quality of End-of-Life Care (EoLC) from a GPs’ perspective using the German version of the General Practice End of Life Care Index (GP-EoLC-I). Methods: Between autumn 2018 and spring 2019, all registered and eligible GPs in two counties in Lower Saxony (n=190) were asked to participate in a survey on EoLC using the German version of the self-assessment questionnaire GP-EoLC-I. The index comprises two subscales: clinical care (13 items) and practice organisation (12 items). The summated index of both subscales measures the quality of EoLC by GPs (25 items; range 14–40). The questionnaire was supplemented by questions on sociodemographic data, indicators for good palliative care (PC) and requirements to improve PC. Quantitative data were analysed by descriptive statistics and free text answers by conventional content analysis according to Hsieh and Shannon. Results: 52 GPs (females: n=16) of 34 practices (single practices: n=26) participated in the study. The mean GP-EoLC-I was 27.5 (SD 4.5). The items revealed potential for improvement: systematic identification of patients with potential PC needs, multidisciplinary case conferences to discuss PC patients, application of care protocols and symptom assessment tools, documentation of patients’ wishes and beliefs as well as inclusion of family and carers. Regarding the indicators for good PC, the most relevant indicators from the GPs’ perspective were collaboration and coordination, integration of relatives, advance care planning and documentation. As requirements to improve PC, GPs highlighted further training and the use of standardised tools such as instruments to support the systematic identification of PC patients. Conclusions: To our knowledge for the first time in Germany, an internationally tested self-assessment questionnaire measuring the quality of EoLC by GPs was applied. The GP-EoLC-I in this study was slightly lower than the index of GPs in the United Kingdom. Including relatives and family carers, implementing tools to support early identification of PC patients and strengthening cooperation between GPs and other stakeholders in PC may be promising approaches to improve general PC and EoLC in Germany.